Features and implications of Emerging Sources Citation Index (Thomson Reuters): Journals in a transitional status - Repiso, Rafael; Torres-Salinas, Daniel (Anuario ThinkEPI, 2016)
With the launch of the Emerging Sources Citation Index (ESCI), Thomson Reuters has created a set of expectations. The Web of Science has become the most comprehensive research platform of journal evaluation. ESCI acts as the waiting room before Thomson technicians check whether journals meet the quality requirements to be indexed in the Science Citation Index (SCI), Social SCI, and Arts & Humanities Citation Index databases. ESCI is characterized by its multidisciplinary coverage and its increase in geographic coverage, now reaching non Anglo-Saxon countries. ESCI increases Thomas Reuters range without sacrificing the quality of its reference products. In addition, it contributes to the transparency of the evaluation and selection process.